2020
DOI: 10.1111/adb.12978
|View full text |Cite
|
Sign up to set email alerts
|

Impaired hypothalamic feedback dysregulates brain glucocorticoid signaling in genetically‐selected Marchigian Sardinian alcohol‐preferring rats

Abstract: Genetically‐selected Marchigian Sardinian alcohol‐preferring (msP) rats display comorbid symptoms of increased alcohol preference and elevated anxiety‐like behavior. Heightened stress sensitivity in msPs is influenced by genetic polymorphisms of the corticotropin‐releasing factor receptor in the central nucleus of the amygdala (CeA), as well as reduced influence of anti‐stress mechanisms that normally constrain the stress response. Given this propensity for stress dysregulation, in this study, we expand on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 62 publications
3
8
0
Order By: Relevance
“…A major finding of this study was that msPs display enhanced anxiety-like behaviors versus non-selected Wistar counterparts in an array of novel behavioral paradigms that are closely associated with stress disorders (e.g., PTSD). The latter finding is consistent with prior work from our laboratory demonstrating that msPs display enhanced anxiety-like behavior in the NIH and EPM [30] and marble-burying tasks [20]. Prior reports also have revealed that msPs display greater anxiety and depressive-like behaviors on numerous behavioral paradigms involving stress and anxiety.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…A major finding of this study was that msPs display enhanced anxiety-like behaviors versus non-selected Wistar counterparts in an array of novel behavioral paradigms that are closely associated with stress disorders (e.g., PTSD). The latter finding is consistent with prior work from our laboratory demonstrating that msPs display enhanced anxiety-like behavior in the NIH and EPM [30] and marble-burying tasks [20]. Prior reports also have revealed that msPs display greater anxiety and depressive-like behaviors on numerous behavioral paradigms involving stress and anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, we found that male msP rats display increased GR phosphorylation at serine 232, a site that is functionally associated with higher transcriptional activity, in the central nucleus of the amygdala (CeA) [20]. This is consistent with several reports demonstrating that GR phosphorylation is also increased in the CeA of alcohol-dependent rats during acute withdrawal [21].…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations